The Influence of the School towards Students’ Indiscipline - Nwokoji, Chukwuemeka (NIU Journal of Social Sciences; Vol 10 No 3 (2024): NIU Journal of Social Sciences, Vol. 10 No. 3, September 2024DO - 10.58709/niujss.v10i3.1990, 2024)
The purpose of this study was to find out the how School management factors influence indiscipline in some selected secondary schools in Rivers State. Applying survey method through questionnaires, it used samples from secondary schools’ students in Rivers State. This study, as much as possible has revealed that such factors as parent’, lapse in their responsibilities towards their children, inadequate amenities in school, lack of teachers’ sincerity and devotion to duty and students’ indifference to study, all contribute to indiscipline and poor performance in schools. The theory of classroom discipline and reinforcement by Skinner was adopted in this work. The instrument used was questionnaire constructed by the investigator. Items on the questionnaire were designed to elicit information on the likely determinants of cases of students’ indiscipline. The results were calculated in percentages. The findings indicated that certain Government factors influence students’ indiscipline. It was discovered that these have adverse social and psychological effect on academic growth. Based on the findings, suggestions are made to the appropriate agencies dealing with students’ discipline and academic growth. It is hoped that these suggestions will check the existence of indiscipline in schools which may be on step to enhancing good academic performance by students. Keywords: Reinforcement, Indiscipline, Government, Discipline, Skinner, Academic Performance, Respondents, Truancy, Students.